Pengaruh Produk, Harga Dan Iklan Terhadap Keputusan Pembelian Pada Pasta Gigi Pbpsodent Di Surabaya Timur - Lilik Indrawati (BIP's JURNAL BISNIS PERSPEKTIF, 2011)
Nowadays, people are getting aware of the importance of keeping mouth and teeth healthy. One of the products which offer dental care is toothpaste which comes in many different brands. To understand better what their consumer want, therefore the producers of toothpaste make use the consumer behavior study so that their product is acceptable by their consumers. Toothpaste was first produced by Dresden Chemical Laboratory Lingner, which is now known as Lingner Werke AG in Germany in 1892. Back then toothpaste came in the form of mouthwash liquid. The most famous toothpaste in 1900 is "Odol" Mouthwash. It was largely used in Europe. (source: http://www.forum.otomotifnet.com/forum/showthread.php) It is the reason why in Indonesia, people knew toothpaste as "odol". It is the generic name used by the consumer to refer to any toothpaste. There are so many brands of toothpaste in market. That is a reason why PT Unilever Indonesia Tbk. wants to know what variables can influence the consumers' decision in buying toothpaste, and therefore increasing the demand of Pepsodent. The objective of the study is to find out whether variables such as price, product and commercial can partially and simultaneously influence the consumers' decision to buy Pepsodent in East Surabaya. The hypothesis of the study is the variables of price, product and commercial would partially, simultaneously and significantly influence the decision of the consumers in buying Pepsodent in East Surabaya. The result of the study is obtained using Slovin formula with Random Sampling. The data analysis technique used in this study is a double linier regression analysis. It is concluded that variable product (X1), variable price (X2) and variable commercial (X3) partially and simultaneously give a significant influence towards the consumers' decision in buying Pepsodent in East Surabaya. This result is acceptable because the first hypothesis F count (60,280) > F table (2. 70) and the second hypothesis thot is variable of product, price and commercial partially will give significant influence towards the consumers' decision in buying Pepsodent in East Surabaya. The result of partial test variable of product (X1) t count (4,416) > t table ( 1,985) so HO is rejected and H1 is accepted, that means product (X1) gives significant influence towards the decision in buying. The result of partial test variable of price (X2) t count (4,727) > t table (1,985), so HO is rejected and H1 is accepted, that means price (X2) gives significant influence towards the decision in buying. The result of partial test variable of commercial (X3) t count (7,877) > t table ( 1,985), so HO is rejected and H1 is accepted that means commercial (X3) gives significant influence towards decision in buying. The most dominant influence towards the decision in buying is commercial. It is showed by the result of partial determination coefficient (0,393 or 39,3%); which is the higher compared to other free variables.